TEACHERS' EFFORTS IN INCREASING STUDENTS' MOTIVATION FOR LEARNING THE ISLAMIC RELIGION AT MADRASAH ALIYAH NURUL JADID - Miftahussurur, Miftahussurur (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
Noting the benefits of motivation and the lack of Islamic teachers in motivating students, the efforts of Islamic teachers need to be improved. This study aims to determine the efforts of Islamic teachers in increasing student motivation, to know and describe the form of motivation of Islamic teachers in motivating students and to know the role of Counseling Guidance teachers in motivating students. This research is a descriptive qualitative research. Data collection used in the research is observation, interview and documentation. The results showed the teacher's efforts in increasing student motivation, namely by stimulating students, secondly providing realistic expectations, thirdly giving awards, and fourthly directing students' behavior. The form of motivation that is often given by Islamic religion teachers varies greatly, but the form of motivation that is often used by teachers in increasing student motivation is in the form of grades, where grades can improve poor test scores. The role of counseling guidance teachers in increasing student motivation is as mentors and counselors. In essence, motivation to learn Islamic religion is a trait from within students that can increase and decrease students' interest and effort to behave in learning.